Repurposing autophagy regulators in brain tumors. Issue 2 (4th March 2022) - Petrosyan, Edgar; Fares, Jawad; Cordero, Alex; Rashidi, Aida; Arrieta, Víctor A.; Kanojia, Deepak; Lesniak, Maciej S.
Abstract: Malignant brain tumors, such as glioblastoma multiforme (GBM) and brain metastases, continue to be an unmet medical challenge. Despite advances in cancer diagnostics and therapeutics, tumor cell colonization in the central nervous system renders most treatment options ineffective. This is primarily due to the selective permeability of the blood‐brain barrier (BBB), which hinders the crossing of targeting agents into the brain. As such, repositioning medications that demonstrate anticancer effects and possess the ability to cross the BBB can be a promising option. Antidepressants, which are BBB‐permeable, have been reported to exhibit cytotoxicity against tumor cells. Autophagy, specifically, has been identified as one of the common key mediators of antidepressant's antitumor effects. In this work, we provide a comprehensive overview of US Food and Drug Administration (FDA)‐approved antidepressants with reported cytotoxic activities in different tumor models, where autophagy dysregulation was demonstrated to play the main part. As such, imipramine, maprotiline, fluoxetine and escitalopram were shown to induce autophagy, whereas nortriptyline, clomipramine and paroxetine were identified as autophagy inhibitors. Sertraline and desipramine, depending on the neoplastic context, were demonstrated to either induce or inhibit autophagy. Collectively, these medications were associated with favorable therapeutic outcomes in a variety of cancer cell models, including brain tumors. Abstract :